PENINGKATAN KEMAMPUAN BERPIKIR KREATIF SISWA SMA DENGAN PENDEKATAN OPEN ENDED - Mariam Ar Rahmah; Sumpena Rohaendi (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2020)
The lack of student’s creative thinking ability was the background of this research. A learning that can make students think creative was needed for bringing up to creative ideas which can be found in the open-ended approach. The objective of this research was to analyze the effect of open-ended approach and to compare the open-ended approach with the expository approach. Quasy experiment method with control group pretest and posttest design to analyze the elevation of student’s creative thinking abilities was conducted on this research, while test and nontest were taken as the instrument. The test consists of questions in which indicators can assess student’s creative thinking skills and nontest questions in the form of questionnaires to see student’s responses. This research resulted that student's creative thinking ability using the open-ended approach was not better than the expository approach. Nevertheless, it was known that students' responses to the open-ended approach were more interesting than the expository approach. By this research result, further research is needed to confirm research result. Keywords: Creative Thinking Ability, Open-Ended Approach, Student Learning Response